Analysis of The Implementation of The Pegadaian Digital Service (PDS) Application on Financial Performance at PT. Pegadaian Regional Office 1 Medan - Samosir, Poppy Marlina; Tiara , Shita; Hanafi, Reza; Fauzi, Indra (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research is entitled The Effect of Implementing the Pegadaian Digital Service (PDS) Application on Financial Performance at PT. Pegadaian 1 Medan Regional Office. PT. Pegadaian is a business entity that operates in the field of gold pawn services. PT. Pegadaian implements an application system called Pegadaian Digital Service (PDS). The purpose of this research is to determine the effect of implementing the Pegadaian Digital Service (PDS) application on financial performance at PT. Pegadaia Regional Office 1 Medan. The research method used is quantitative research. The data obtained in this research is secondary data. The number of samples used was 36 samples, namely the 2020-2022 Financial Report and a population of 72 from 2015-2017 and 2020-2022 with a time span of 2020-2022. The data analysis test uses a linear regression analysis test with a value of Y= 8.158+ 0.199x, which means there is a positive relationship between the implementation of the Pegadaian Digital Service (PDS) application and financial performance of 19.9% and a normality test to ensure data suitability. The data processing used in this research uses SPSS 23. The results of the research show that partially the implementation of PDS has a significant effect on the financial performance of PT. Pegadaian 1 Medan Regional Office. PDS Application Contribution to Financial Performance (ROA) was 23.8%. t count > t table (3.256>1.691) with a significance level of 0.03<0.05. It was found that the Pegadaian Digital Service (PDS) application had an effect on financial performance.